2017
DOI: 10.1038/nn.4635
|View full text |Cite
|
Sign up to set email alerts
|

Seeing faces is necessary for face-domain formation

Abstract: Here we report that monkeys raised without exposure to faces did not develop face patches, but did develop domains for other categories, and did show normal retinotopic organization, indicating that early face deprivation leads to a highly selective cortical processing deficit. Therefore experience must be necessary for the formation, or maintenance, of face domains. Gaze tracking revealed that control monkeys looked preferentially at faces, even at ages prior to the emergence of face patches, but face-deprive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
195
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 273 publications
(216 citation statements)
references
References 61 publications
10
195
2
2
Order By: Relevance
“…U.D.’s normal face recognition also challenges the conclusion that face selectivity and its anatomical localization is genetically coded and that subsequent compensation is not possible (Farah et al, 2000). In contrast, our results favor dynamic reorganization and fine-tuning in the functional architecture of cognition over development (Johnson, 2011) and argue for the critical role of experience in shaping the underlying circuitry (Arcaro et al, 2017). …”
Section: Discussioncontrasting
confidence: 56%
“…U.D.’s normal face recognition also challenges the conclusion that face selectivity and its anatomical localization is genetically coded and that subsequent compensation is not possible (Farah et al, 2000). In contrast, our results favor dynamic reorganization and fine-tuning in the functional architecture of cognition over development (Johnson, 2011) and argue for the critical role of experience in shaping the underlying circuitry (Arcaro et al, 2017). …”
Section: Discussioncontrasting
confidence: 56%
“…For years, people thought that humans were born with an FFA. However, a recent study in which scientists raised baby monkeys making sure they never saw a face revealed that, as a result, they had no FFA and they also did not look at faces more than other objects [4]. This study showed that experience with faces is required for us to become face experts.…”
Section: Are We Born With a Face Detector?mentioning
confidence: 73%
“…Under this view, one might expect individual differences in neonatal imitation to predict only very early forms of social cognition, such as the tendency to maintain mutual gaze with a caregiver (see Heimann, ), and not the forms we measured here. Of course, both of these alternative explanations presuppose that neonatal imitation is a genuine phenomenon, which recent evidence suggests is unlikely (Arcaro et al, ; Barbosa, ; Cracco et al, ; Keven & Akins, ; de Klerk et al, ; McKyton et al, ; Oostenbroek et al, ; Redshaw, ).…”
Section: Discussionmentioning
confidence: 99%
“…We were compelled to conclude, therefore, that rather than providing the foundation for a definitive study of neonatal imitation's function, our data instead challenged the very existence of neonatal imitation itself. This unforeseen conclusion has since been substantiated by several other works: A comprehensive sensorimotor analysis suggesting that neonates lack voluntary, cortical control over tongue protrusion, thus making intentional imitation of this action implausible (Keven & Akins, ); A study suggesting that previously blind, newly sighted children show greatly impaired automatic imitation of manual actions, meaning that this capacity is either not innate or vulnerable to degradation in specific domains (McKyton, Ben‐Zion, & Zohary, ); A study showing that mothers’ tendency to imitate their 4‐month‐old infants’ actions predicted these infants’ own rudimentary signs of imitation (measured by EMG), suggesting that infants may learn to imitate via repeated associative pairings of their own and others’ actions (de Klerk, Lamy‐Yang, & Southgate, ); A systematic meta‐analysis suggesting that automatic imitation in adults is also best explained by an associative learning framework (Cracco et al, ), meaning that the existence of neonatal imitation would require the non‐parsimonious addition of a second, innate mechanism to explain the same phenomenon; A statistically robust re‐analysis of data previously used to support the existence of neonatal imitation in rhesus macaques (Paukner, Pederson, & Simpson, ), showing that neonatal macaques have in fact failed to produce imitative actions at levels greater than chance (Redshaw, ); A study suggesting that newborn primates are not born with an innate capacity to recognize faces, meaning they would be unable to link the actions of other faces with those of their own face (Arcaro, Schade, Vincent, Ponce, & Livingstone, ); and An unpublished PhD thesis that similarly found no evidence of neonatal imitation in a longitudinal study of 90 human infants measured at four time points (Barbosa, ). …”
Section: Introductionmentioning
confidence: 91%